Computers in railways X computer system design and operation in the railway and other transit systems - Allan, J. (John) (WIT transactions on the built environment, 2006)
This book updates the use of computer-based techniques, promoting their general awareness throughout the business management, design, manufacture and operation of railways and other advanced passanger, freight and transport systems.